Reconfigurable Voltage-Mode First-Order Multifunction Filter Employing Second-Generation Voltage Conveyor (VCII) With Complete Standard Functions and Electronically Controllable Modification - Winai Jaikla; Surasak Sangyaem; Piya Supavarasuwat; Fabian Khateb; Shahram Minaei; Tomasz Kulej; Peerawut Suwanjan (My University, 2023)
In this contribution, the realization of a first-order, two-input, single-output voltage-mode multifunction filter employing a second-generation voltage conveyor (VCII) is described. The proposed first-order versatile filter is extremely simple, composed of a single VCII and three passive devices. Because of its low output impedance, the output voltage node can be easily cascaded with other voltage-mode configurations without the requirement of any buffers. In the same circuit topology, the proposed first-order filter provides various filtering functions: inverting and non-inverting low-pass (LPF), inverting and non-inverting high-pass (HPF), as well as inverting and non-inverting all-pass (APF). The digital method allows the selection of output first-order filtering functions without the need for additional circuits such as inverting or double-gain amplifiers. Furthermore, the pass-band gain of the low-pass and high-pass responses can be adjusted by varying the resistance or capacitance values without influencing the pole frequency as well as the phase response. The influence of VCII's current/voltage gain errors and parasitic elements on filtering performance is also investigated. Moreover, the modification of the proposed lagging phase all-pass filter to achieve electronic controllability is also proposed by replacing the passive resistor with the operational transconductance amplifier (OTA). The $0.18\mu \text{m}$ TSMC CMOS structure of the VCII employed in the proposed filter operates in the subthreshold region and utilizes the bulk-driven technique (BD), enabling it to operate with 0.4V supply voltage and consuming 383 nW of power. The total harmonic distortion (THD) of the LPF with an applied input voltage $V_{inpp}=300$ mV @ 50Hz is -49.5 dB. An application example as a quadrature sinusoidal oscillator realized from the proposed first-order allpass filter and lossless integrator is also included. The performance of the proposed reconfigurable voltage-mode first-order filter is simulated and experimentally tested using a commercially available AD844 IC-based VCII with ±5 V power supply.
Keywords: Current conveyor; All-pass filter; Electronic filter topology; Operational transconductance amplifier; Analog and Mixed-Signal Circuit Design